A imaginação cega: mecanismos de indeterminação na prática artística contemporânea - Miguel Leal (2009)
This is a study about a certain unthought in art which is associated with the presence of chance and indetermination. Its subject is therefore the instant in which the artist's intention and the precision of his tools cease to define the predictability of his own actions - even if only as a gesture of enunciation or artificialisation of chance. Focusing on those visual arts that bring together random elements and planned actions, unpredictability and determinism, chance and control, we try to question the aporetic nature of an aesthetic game that combines absolute surprise with its methodological and processual anticipation. How should we approach the results of what is unthought and unexpected in art and its thought? What are the distinctive features in contemporary artistic practice of the presence of chance and indetermination in the processual mechanisms of art? Assuming that art is something made from its own making, our first step is to propose the notion of almost-ideal game - based on a rereading of Deleuze - to define chance in art as operative, coordinating plasticity, experimentation and imagination as its motors. Blind imagination thus emerges simply as another name for the hesitant experimentation through which the unthought in art is accessed. As the operative blindness of art results from the unpredictability of its media, of its machines, the mechanisms of indetermination in artistic practice actually coincide with the specific machinic processes of aesthetic experimentation. It is then suggested, in line with Agamben, that only in an era of ubiquitous technique can art radically think its media, making them (in)operative; consideration is also given to the principle of a pure mediality which is grounded on aesthetic experimentation or, in other words, to the principle of an art that shows itself capable of testing its media to the limit. Machinic dysfunctionality and the obsolescence of the media are thus two of the main ways of inducing that vertigo that makes things stutter and react unexpectedly and surprisingly. Embodying the almost perfect figure of a machine that produces and induces production - a machine of sharing and interference that the artist must not hamper or control, since important things always happen in a surprising way, never where we expect them -, we give the name technological unconscious to this degree of indetermination and surprise that is the reserve of any machine. In response to the declared intention of focusing analysis on the genuine operative processes of doing-thinking in art, case studies are presented throughout the work, from the classical tradition of accidental images to Alexander Cozens or from August Strindberg to Duchamp, finally arriving at discussion on the problems posed by this thesis regarding the field of contemporary art. It can be concluded from this study that technology offers, or can offer, fertile terrain for the unthought, for the random and for the unexpected, linking those vital ingredients of art which are experimentation, plasticity and blind imagination. The attention - fascinated or defascinated - paid by art to its machines and their mechanisms of indetermination thus defines, in operative terms, one of the most important distinctive features of the presence of chance in current artistic practice.